Mystery isle - St. George, Judith, 1931- (New York : Sleuth/Puffin, 2007)
What seems a harmless enough trip to the family's ancestral home on a Maine island turns into something much more dangerous for thirteen-year-old Kim.
Accelerated Reader AR
Keywords: Islands -- Juvenile fiction; Great-grandfathers -- Juvenile fiction; Islands -- Fiction; Great-grandfathers -- Fiction; Mystery and detective stories; Maine -- Juvenile fiction; Maine -- Fiction; Mystery fiction